COMMUNITY PARTICIPATION IN PAYING LAND AND BUILDING TAX IN BITUNG BARAT DUA SUB-DISTRICT MAESA BITUNG CITY - Mantiri, Jeane; Pangkey, Itje; Onibala, Nancy M; Makaminang, Farel Alfabio (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
This research aims to describe community participation in paying land and building taxes in Bitung Barat Village, Dua Maesa District. The research method used is descriptive qualitative. Research location in West Bitung Village Two Maesa District, Bitung City. Data collection uses observation, interview and documentation techniques. Data analysis through data reduction, data presentation and drawing conclusions. The validity of the data used in research, namely Credibility, Transferability, Dependability, Confirmability. The results of the research show that it is concluded that community participation in paying land and building taxes in Bitung Barat Dua Village, Maesa District is based on 2 indicators, namely: 1). Related to the reason why people who are taxpayers do not pay taxes is due to a lack of motivation from the taxpayer community regarding the importance of paying land and building taxes. 2) the efforts made by the government to foster motivation and understanding among the taxpayer community, namely outreach to the taxpayer community, have not been accepted by the community, this means that there are still many people who are in arrears and are lazy about paying taxes. Penelitian ini bertujuan untuk mendeskripsikan partisipasi masyarakat dalam membayar pajak bumi dan bangunan di Kelurahan Bitung Barat Kecamatan Dua Maesa. Metode penelitian yang digunakan adalah deskriptif kualitatif. Lokasi Penelitian di Kelurahan Bitung Barat Dua Kecamatan Maesa Kota Bitung. Pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi. Analisis data melalui Reduksi Data, Penyajian Data dan Penarikan Kesimpulan. Keabsahan data yang digunakan dalam penelitian, yaitu Credibility, Transferability, Depenability, Confirmability. Hasil penelitian menunjukkan bahwa menyimpulkan bahwa partisipasi masyarakat dalam membayar pajak bumi dan bangunan di Kelurahan Bitung Barat Dua Kecamatan Maesa berdasarkan 2 indikator yaitu: 1). Terkait dengan penyebab masyarakat yang merupakan wajib pajak, tidak membayar pajak karena kurangnya motivasi dari masyarakat wajib pajak mengenai pentingnya membayar pajak bumi dan bangunan. 2) upaya yang dilakukan pemerintah dalam menumbuhkan motivasi dan pemahaman bagi masyarakat wajib pajak yaitu sosialisasi kepada masyarakat wajib pajak belum dapat diterima oleh masyarakat, hal ini masih banyak masyarakat yang menunggak, malas, untuk membayar pajak.